2008
DOI: 10.1016/j.ijrobp.2007.07.2342
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Institution Prospective Trial of Reduced-Dose Craniospinal Irradiation (23.4 Gy) Followed by Conformal Posterior Fossa (36 Gy) and Primary Site Irradiation (55.8 Gy) and Dose-Intensive Chemotherapy for Average-Risk Medulloblastoma

Abstract: Purpose/Objective-Limiting neurocognitive sequelae of radiation therapy (RT) has been an objective in the treatment of medulloblastoma (MB). Conformal RT to less than the entire posterior fossa (PF) after craniospinal irradiation (CSI) may reduce neurocognitive sequelae and requires evaluation. October 1996 and August 2003, 86 patients, 3-21 years of age, with newly diagnosed, average-risk MB were treated on a prospective, IRB-approved, multi-institution trial of risk-adapted RT and dose-intensive chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(49 citation statements)
references
References 40 publications
(47 reference statements)
0
47
0
Order By: Relevance
“…The latter is indicated due to the high rate of relapse within the posterior fossa. Studies conducted by the International Society of Pediatric Oncology (SIOP) and the Children’s Oncology Group, among others, have supported a reduction in the CSI dose to 23.4-24 Gy with the addition of adjuvant chemotherapy [50, 51]. ACNS0331, a COG study of further CSI dose-reduction to 18 Gy in young children (aged 3 to 7 years) is currently underway.…”
Section: Treatment – General Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is indicated due to the high rate of relapse within the posterior fossa. Studies conducted by the International Society of Pediatric Oncology (SIOP) and the Children’s Oncology Group, among others, have supported a reduction in the CSI dose to 23.4-24 Gy with the addition of adjuvant chemotherapy [50, 51]. ACNS0331, a COG study of further CSI dose-reduction to 18 Gy in young children (aged 3 to 7 years) is currently underway.…”
Section: Treatment – General Principlesmentioning
confidence: 99%
“…ACNS0331, a COG study of further CSI dose-reduction to 18 Gy in young children (aged 3 to 7 years) is currently underway. Similarly, several studies have demonstrated that the posterior fossa radiation volume may be safely reduced through conformal treatment to the tumor bed, allowing for sparing of normal structures, including the temporal lobes, hypothalamus, and cochleae, although this is not a universally accepted practice [51-53]. Similarly, the use of IMRT or proton beam therapy can reduce exposure to the heart and liver during CSI [54-57].…”
Section: Treatment – General Principlesmentioning
confidence: 99%
“…The conventional dose is 30 to 36 Gy of craniospinal irradiation and a boost to a total of 55.8 Gy to the primary brain site. 113,115 A lower craniospinal dose of 23.4 Gy, combined with chemotherapy, has gained popularity for average-risk patients to lessen side effects while maintaining 55.8 Gy to the posterior fossa, 111,116,117 although one randomized trial found an increased relapse risk with dose reduction. 118 SRS demonstrated safety and efficacy in a small series of 12 adult patients with residual or recurrent disease.…”
Section: Medulloblastoma and Supratentorial Primitive Neuroectodermalmentioning
confidence: 99%
“…The use of postirradiation chemotherapy to allow radiation dose reduction is becoming increasingly common especially for children, 116,117 but optimal use of adjuvant chemotherapy is still unclear for adult patients. 110112,120,121 A phase III study that enrolled more than 400 patients between ages 3 and 21 years to receive postirradiation cisplatin-based chemotherapy regimens recorded an encouraging 86% 5-year survival.…”
Section: Medulloblastoma and Supratentorial Primitive Neuroectodermalmentioning
confidence: 99%
“…Adjuvant cisplatin-based chemotherapy is also used. This approach results in a 5-year survival rate in up to 85% of standard risk (SR) cases [1-3]. …”
Section: Introductionmentioning
confidence: 99%